Acute atrial ischemia associates with early but not late new-onset atrial fibrillation in STEMI patients treated with primary PCI: relationship with in-hospital outcomes. Issue 5 (November 2021) - Biccirè, Flavio Giuseppe; Pastori, Daniele; Torromeo, Concetta; Acconcia, Maria Cristina; Capone, Silvia; Ferrari, Ilaria; Pannarale, Giuseppe; Paravati, Vincenzo; Gaudio, Carlo; Tanzilli, Gaetano; Barillà, Francesco
Abstract: Background: New-onset atrial fibrillation (NOAF), both early (EAF) or late (LAF), may complicate ST-segment elevation myocardial infarction (STEMI). The mechanisms underlying EAF or LAF are poorly described. We investigated atrial branch occlusion and EAF or LAF onset in STEMI patients undergoing primary percutaneous coronary intervention. Methods: This was a retrospective cohort study including 155 STEMI patients. Patients were divided into 3 groups: sinus rhythm (SR), EAF, or LAF. Clinical characteristics, angiographic features including occlusion of atrial branches, namely ramus ostia cavae superioris (ROCS), atrio-ventricular node artery (AVNA), right intermediate atrial artery (RIAA), and left intermediate atrial artery, were assessed. We also investigated in-hospital adverse events (AEs) and death. Results: Mean age was 63.8±11.9 years; 78.7% were men. NOAF was detected in 22 (14.2%) patients: 10 (6.4%) EAF and 12 LAF (7.7%). Compared to EAF, LAF patients were older ( p =0.013), with higher GRACE risk score ( p =0.014) and Killip class ( p =0.015), depressed ejection fraction ( p =0.007), elevated filling pressures ( p =0.029), higher C-reactive protein ( p =0.014) and more with thrombolysis in myocardial infarction flow <3 ( p =0.015). Compared to SR, EAF was associated with higher prevalence of occluded ROCS ( p =0.010), AVNA ( p =0.005), and RIAA ( p <0.001). Moreover, EAF patients had more frequently ≥2 diseased atrial branches than SR (19.5%, p <0.001) and LAF (25%, p <0.030) patients. LAF patients had a higher in-hospital AEs ( p =0.019 vs SR; p =0.029 vs EAF) and death ( p =0.004 vs SR). Conclusions: The occlusion of atrial branches is associated with EAF but not LAF following STEMI. LAF patients had worse in-hospital AEs and mortality. Highlights: Early and late atrial fibrillation (AF) after ST-segment elevated myocardial infarction have recently been described. Whether atrial ischemia is associated with early or late AF is unknown. Atrial branch occlusion is higher in patients with early but not late AF episodes. Early AF episodes are associated with better in-hospital outcomes and mortality. Graphical abstract: Image, graphical abstract